Arabic Letter Wheel Accommodates Hijaiyah Decoding In Learners With Motor Impairments: Roda Huruf Arab Mengakomodasi Dekode Hijaiyah Pada Pembelajar Dengan Gangguan Motorik - Abdul Rajak; Lantip Diat Prasojo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Inclusive education demands equal access to quality educational services for all individuals, including those with physical limitations. Specific Background Conventional Islamic education requires fine motor skills for recognizing and pronouncing alphabetic symbols, creating significant learning barriers for children born with severe limb deficiencies. Knowledge Gap Existing research predominantly focuses on digital or interactive learning tools that still require manual dexterity, leaving a lack of empirical evidence on accessible pedagogical interventions specifically designed for individuals lacking upper and lower limbs. Aims This study applies a Single Subject Research approach with an A-B-A design to evaluate a novel rotational instrument as an adaptive instructional medium for a student with congenital physical disabilities. Results The adaptive rotational mechanism significantly elevated the participant's orthographic recognition performance from a 59.48% baseline to 62.58% during the intervention, ultimately reaching a highly stable 71.03% in the post-intervention maintenance phase. Novelty This research uniquely demonstrates that integrating multisensory visual and auditory stimuli through a motor-independent mechanical tool can successfully replace traditional dexterity-reliant methods in special education. Implications Rural inclusive schools must adopt accessible, game-based interventions to ensure equitable participation, long-term skill retention, and independent literacy acquisition for marginalized students with severe physical limitations. Highlights An interactive multisensory pedagogical instrument significantly elevates early script recognition without requiring manual dexterity. Quantitative assessments confirmed stable long-term retention of alphabetical mastery following the withdrawal of the intervention. Accessible game-based instructional strategies foster independent education and active engagement within rural inclusive environments. Keywords Inclusive Education; Congenital Physical Disability; Multisensory Learning; Single Subject Research; Maintenance Effect